Utilizing Phonics Instruction for Teaching Reading to Young Learners - Rizky Riski Riski; Ratna Dewanti (Fakultas Keguruan dan Ilmu Pendidikan Universitas Tanjungpura, 2022)
Reading is one of the basic skills in English. Reading is a receptive skill which allows students to acquire a wide range of literacy (Tuhumury & Nikijuluw, 2020). Thus, we need to pay more attention on how to have successful teaching reading especially for young learners. Teaching reading by utilizing phonics instruction has been proven to improve student’s reading skill. This present study is aimed at exploring the application of phonics instruction for teaching reading to young learners in order to get a better understanding of the effectiveness of utilizing phonics for reading to young learners. Three videos of teaching by teacher Jady were chosen to be the data source of this study. The findings showed that there were several stages that were used by teacher Jady in order to have successful phonics instruction to teaching reading to young learners. The stages are introducing letter sounds, teaching blending two sounds which consist of Consonant-Vowel and teaching blending three sounds which consist of Consonant-Vowel-Consonant.